Identification of students' multiple achievement and social goal profiles and analysis of their stability and adaptability - Gonçalves, Teresa (2017)
The present study moves to a more comprehensive understanding of the dynamics of student's goal orientation by jointly analyzing a variety of students' achievement goals together with students' social goals, and their combined effects. Using a person-centered approach (latent cluster analysis) the study identified students' (N = 386) goal profiles, analysed in what ways achievement and social goals are combined, and tested whether profile groups differed on their motivational and academic adaptability. Moreover, this study analysed stability and change in students' multiple goal profiles across the transition into secondary school (from 9th to 10th grade). Six distinct profiles of achievement and social goals emerged showing construct stability over time. Across profiles findings showed that prosocial and social responsibility goals are connected with mastery goals, but seem more difficult to reconcile with performance-competitive goals. In general, findings highlighted the positive role of both mastery and social goals in students' academic outcomes (differences between profiles ranging from η 2 0.03 to 0.18), but also showed that distinct goal combinations may be compatible with students' motivation and academic success.